Recta y planos perpendiculares - Cotrina Vsquez, Yeltsind Juan Linker (2018)
The present work of professional proficiency has the title "Straight and Perpendicular Planes"; whose development of the learning session has been based on various bibliographical sources of consultation such as research, books and thesis; as well as application of knowledge acquired during the academic years of my training, whose conclusions indicate that; understanding, analysis and resolution on straight lines and perpendicular planes help us determine the development of problematic situations that arise in our daily life, without neglecting the humanistic values and democratic principles that may arise during the process of their solution, Respecting itself and other people, also presenting solidarity and equity promoting intercultural dialogue. Taking into account also that during the development of the didactic processes will allow to better organize the learning and the knowledge of the students, joined the participative and collaborative activity allowing to integrate the group to all the students. Taking a lot of consideration as the Plya method in the area of mathematics, since knowledge is constructed from different criteria.